Carbon allotrope hybrids advance thermoelectric development and applications. (May 2021) - Liu, Wei-Di; Yu, Yao; Dargusch, Matthew; Liu, Qingfeng; Chen, Zhi-Gang
Abstract: As an emission-free energy conversion technology, thermoelectric technology has been considered an essential component in solving the global energy crisis. Carbon allotrope hybrids, with relatively low cost, high performance and engineerable mechanical strength and flexibility, are attracting increasing research interest. The key challenge of developing carbon allotrope hybrid thermoelectric applications lies in material performance enhancement, which is further restricted by enhancing the electrical performance, refraining the lattice thermal conductivity and engineering the mechanical properties. Compositing carbon allotropes to enhance electrical transport properties should be mainly attributed to the material orientation effect which increases the carrier mobility or to the energy filtering effect which increases the Seebeck coefficient. The reduced lattice thermal conductivity due to the formation of carbon allotrope hybrid is derived from various additional phonon scattering features. Furthermore, carbon allotrope-compositing is also effective in enhancing the mechanical properties of thermoelectric materials, which can potentially further widen the variety of applications of these materials. A key opportunity in better utilizing the flexibility of carbon materials is deploying them as stents. Carbon allotrope hybrids can provide a pathway such that rigid thermoelectric materials can be designed into flexible thermoelectric materials. Finally, we point out future research directions for carbon-hybrid thermoelectric materials. Graphical abstract: Image 1 Highlights: Overview of carbon allotrope-compositing methods. Summarized influence of carbon allotropes on thermoelectric performance. Summarized influence of carbon allotropes on mechanical properties. Summary of carbon allotrope-hybrids related thermoelectric module design. Pointing out research directions of thermoelectric carbon allotrope-hybrids.